Non-aqueous electrolyte secondary battery

By using specific graphite particles in the negative active material layer of the nonaqueous electrolyte secondary battery and concentrating on the outer surface side, and adding diisocyanate compounds to the nonaqueous electrolyte, the battery expansion problem is solved and the battery is significantly improved Safety and stability.

CN114788048BActive Publication Date: 2024-12-24PANASONIC ENERGY CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202080083503.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-06
Filing Date
2020-11-25
Publication Date
2024-12-24
Estimated Expiration
2040-11-25

AI Technical Summary

Technical Problem

The existing nonaqueous electrolyte secondary batteries produce a large amount of gas during storage at high temperatures, causing the battery to expand, affecting safety, and difficult to effectively suppress.

Method used

The negative electrode active material layer contains graphite particles A with an internal void ratio of less than 5% and graphite particles B with 8% to 20%, and is more concentrated on the outer surface side of half of the area on the negative electrode current collector side, and is combined with a nonaqueous electrolyte. Diisocyanate compounds are added to inhibit the decomposition reaction and gas production at high temperatures.

Benefits of technology

It effectively suppresses the amount of battery expansion caused by gas during high temperature storage, and improves the safety and stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114788048B_ABST
    Figure CN114788048B_ABST
Patent Text Reader

Abstract

The present application aims to provide a non-aqueous electrolyte secondary battery capable of suppressing the amount of battery expansion caused by gas generation during high-temperature storage. As one embodiment of the present application, the non-aqueous electrolyte secondary battery comprises a positive electrode, a negative electrode (12), and a non-aqueous electrolyte, wherein the negative electrode (12) comprises a negative electrode collector (40) and a negative electrode active material layer (42) disposed on the negative electrode collector (40), wherein the negative electrode active material layer (42) comprises graphite particles A and graphite particles B as negative electrode active materials, wherein the internal porosity of the graphite particles A is 5% or less, and the internal porosity of the graphite particles B is 8% to 20%, wherein the graphite particles A are contained more in a region (42b) on the outer surface side than in a region (42a) on the negative electrode collector side when the negative electrode active material layer (42) is divided into two equal parts in the thickness direction, and wherein the non-aqueous electrolyte comprises a diisocyanate compound.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a non-aqueous electrolyte secondary battery. Background Art

[0002] Non-aqueous electrolyte secondary batteries using a carbon material as a negative electrode active material are widely used as high energy density secondary batteries.

[0003] For example, Patent Document 1 discloses a non-aqueous electrolyte secondary battery using densified carbon having an internal porosity of 5% or less as a carbon material.

[0004] For example, Patent Document 2 discloses a nonaqueous electrolyte secondary battery using carbon materials including a carbon material A having an internal porosity of 1% or more and less than 23% and a carbon material B having an internal porosity of 23% or more and 40% or less.

[0005] Patent Document 3 discloses that a nonaqueous electrolyte secondary battery using a nonaqueous electrolyte containing a diisocyanate compound can suppress the amount of gas generated during high-temperature storage and suppress the amount of battery expansion.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Laid-Open No. 9-320600

[0009] Patent Document 2: Japanese Patent Application Publication No. 2014-67638

[0010] Patent Document 3: Japanese Patent Application Publication No. 2007-242411 Summary of the invention

[0011] Problems to be solved by the invention

[0012] However, in order to further increase the capacity of non-aqueous electrolyte secondary batteries in the future and ensure the safety of the batteries, it is required to further suppress the gas generation during high-temperature storage to suppress the amount of battery expansion.

[0013] The present application has been made in view of the above circumstances, and an object of the present application is to provide a non-aqueous electrolyte secondary battery capable of suppressing the amount of battery expansion caused by gas generation during high-temperature storage.

[0014] Means used to solve problems

[0015] A nonaqueous electrolyte secondary battery as one embodiment of the present application comprises a positive electrode, a negative electrode, and a nonaqueous electrolyte, wherein the negative electrode comprises a negative electrode collector and a negative electrode active material layer disposed on the negative electrode collector, wherein the negative electrode active material layer comprises graphite particles A and graphite particles B as negative electrode active materials, wherein the internal porosity of the graphite particles A is less than 5%, and the internal porosity of the graphite particles B is 8% to 20%, wherein the graphite particles A are more contained in a region on the outer surface side than in a region on the negative electrode collector side when the negative electrode active material layer is divided into two equal parts in the thickness direction, and wherein the nonaqueous electrolyte comprises a diisocyanate compound.

[0016] Effects of the Invention

[0017] According to one embodiment of the present application, the amount of expansion of the battery due to gas generation during high-temperature storage can be suppressed. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a cross-sectional view of a nonaqueous electrolyte secondary battery as an example of an embodiment.

[0019] Figure 2 It is a cross-sectional view of a negative electrode as an example of an embodiment.

[0020] Figure 3 It is a cross-sectional view of graphite particles in the negative electrode active material layer. DETAILED DESCRIPTION

[0021] A nonaqueous electrolyte secondary battery as one embodiment of the present application comprises a positive electrode, a negative electrode, and a nonaqueous electrolyte, wherein the negative electrode comprises a negative electrode collector and a negative electrode active material layer disposed on the negative electrode collector, wherein the negative electrode active material layer comprises graphite particles A and graphite particles B as negative electrode active materials, wherein the internal porosity of the graphite particles A is less than 5%, and the internal porosity of the graphite particles B is 8% to 20%, wherein the graphite particles A are more contained in a region on the outer surface side than in a region on the negative electrode collector side when the negative electrode active material layer is divided into two equal parts in the thickness direction, and wherein the nonaqueous electrolyte comprises a diisocyanate compound.

[0022] It is believed that the non-aqueous electrolyte containing a diisocyanate compound is suppressed in the decomposition reaction of the non-aqueous electrolyte at the positive electrode under a high temperature environment compared to the non-aqueous electrolyte not containing a diisocyanate compound. In addition, it is believed that, as in the present application, by comparing the negative electrode collector side half of the negative electrode active material layer, the graphite particles A with an internal porosity of less than 5% are more contained in the region of the outer surface side half of the negative electrode active material layer, thereby suppressing the reactivity on the outer surface of the negative electrode active material layer, and therefore, the decomposition reaction of the non-aqueous electrolyte at the negative electrode is suppressed under a high temperature environment. In this way, by suppressing the decomposition reaction of the non-aqueous electrolyte at the positive and negative electrodes under a high temperature environment, the gas generation caused by the decomposition reaction of the non-aqueous electrolyte can also be suppressed, and therefore, the expansion of the battery caused by gas generation during high temperature storage can be suppressed.

[0023] Hereinafter, an example of an embodiment will be described in detail with reference to the accompanying drawings. It should be noted that the non-aqueous electrolyte secondary battery of the present application is not limited to the embodiment described below. In addition, the drawings referred to in the description of the embodiment are schematic drawings.

[0024] Figure 1 It is a cross-sectional view of a nonaqueous electrolyte secondary battery as an example of an embodiment. Figure 1 The non-aqueous electrolyte secondary battery 10 shown includes: a wound electrode body 14 in which a positive electrode 11 and a negative electrode 12 are wound with a separator 13 interposed therebetween, a non-aqueous electrolyte, insulating plates 18 and 19 respectively arranged above and below the electrode body 14, and a battery case 15 for accommodating the above components. The battery case 15 is composed of a case body 16 in a cylindrical shape with a bottom, and a sealing body 17 for sealing the opening of the case body 16. It should be noted that other types of electrode bodies such as a laminated electrode body in which a positive electrode and a negative electrode are alternately laminated with a separator interposed therebetween may be used instead of the wound electrode body 14. In addition, as the battery case 15, examples include cylindrical, square, coin-shaped, button-shaped, and other metal outer cans, and bag-type outer bodies formed by laminating resin sheets and metal sheets, etc.

[0025] The case body 16 is, for example, a metal outer can with a bottomed cylindrical shape. A gasket 28 is provided between the case body 16 and the sealing body 17 to ensure the airtightness of the battery interior. The case body 16 has, for example, a bulging portion 22 in which a part of the side surface bulges inwardly and supports the sealing body 17. The bulging portion 22 is preferably formed in an annular shape along the circumferential direction of the case body 16, and supports the sealing body 17 on its upper surface.

[0026] The sealing body 17 has a structure in which a filter 23, a lower valve body 24, an insulating member 25, an upper valve body 26 and a cover 27 are stacked in order from the electrode body 14 side. The components constituting the sealing body 17 have, for example, a disc shape or a ring shape, and the components except the insulating member 25 are electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected to each other at their respective central portions, and the insulating member 25 is sandwiched between their respective peripheral portions. If the internal pressure of the non-aqueous electrolyte secondary battery 10 rises due to heat caused by an internal short circuit, for example, the lower valve body 24 is deformed and broken in a manner that pushes the upper valve body 26 upward toward the cover 27 side, and the current path between the lower valve body 24 and the upper valve body 26 is cut off. If the internal pressure rises further, the upper valve body 26 breaks, and the gas is discharged from the opening of the cover 27.

[0027] exist Figure 1 In the non-aqueous electrolyte secondary battery 10 shown, the positive electrode lead 20 installed on the positive electrode 11 extends to the sealing body 17 side through the through hole of the insulating plate 18, and the negative electrode lead 21 installed on the negative electrode 12 extends to the bottom side of the shell body 16 through the outside of the insulating plate 19. The positive electrode lead 20 is connected to the bottom plate of the sealing body 17, that is, the lower surface of the filter 23, by welding or the like, and the top plate of the sealing body 17, that is, the cover 27 electrically connected to the filter 23 becomes the positive terminal. The negative electrode lead 21 is connected to the bottom inner surface of the shell body 16 by welding or the like, and the shell body 16 becomes the negative terminal.

[0028] Hereinafter, each component of the nonaqueous electrolyte secondary battery 10 will be described in detail.

[0029] [negative electrode]

[0030] Figure 2 1 is a cross-sectional view of a negative electrode as an example of an embodiment. The negative electrode 12 includes a negative electrode current collector 40 and a negative electrode active material layer 42 provided on the negative electrode current collector 40 .

[0031] The negative electrode current collector 40 is made of, for example, a foil of a metal such as copper that is stable in the potential range of the negative electrode, or a film having the metal disposed on the surface.

[0032] The negative electrode active material layer 42 contains graphite particles as the negative electrode active material. In addition, the negative electrode active material layer 42 preferably contains a binder, etc. The negative electrode 12 can be produced, for example, as follows: a negative electrode mixture slurry containing a negative electrode active material, a binder, etc. is prepared, the negative electrode mixture slurry is applied to the negative electrode collector 40 and dried to form the negative electrode active material layer 42, and the negative electrode active material layer 42 is rolled. It should be noted that the details of the method for producing the negative electrode active material layer 42 will be described later.

[0033] Figure 3 is a cross-sectional view of graphite particles in the negative electrode active material layer. Figure 3As shown, the graphite particle 30 has closed voids 34 (hereinafter referred to as internal voids 34) not connected from the inside of the particle to the particle surface, and voids 36 (hereinafter referred to as external voids 36) connected from the inside of the particle to the particle surface in a cross-sectional view of the graphite particle 30.

[0034] The graphite particles 30 in this embodiment include graphite particles A having an internal porosity of 5% or less, and graphite particles B having an internal porosity of 8% to 20%. From the perspective of suppressing the expansion of the battery caused by gas generation during high-temperature storage, the internal porosity of graphite particles A can be 5% or less, preferably 1% to 5%, and more preferably 3% to 5%. From the perspective of suppressing the expansion of the battery caused by gas generation during high-temperature storage, the internal porosity of graphite particles B can be 8% to 20%, preferably 10% to 18%, and more preferably 12% to 16%. Here, the internal porosity of graphite particles refers to a two-dimensional value obtained by the ratio of the area of ​​the internal voids 34 of the graphite particles to the cross-sectional area of ​​the graphite particles. In addition, the internal porosity of the graphite particles is obtained by the following steps.

[0035] <Method for measuring internal void ratio>

[0036] (1) Exposing the cross section of the negative electrode active material layer. For example, a method of exposing the cross section includes cutting a portion of the negative electrode and processing it using an ion milling device (for example, IM4000PLUS manufactured by Hitachi High-Tech Co., Ltd.) to expose the cross section of the negative electrode active material layer.

[0037] (2) Using a scanning electron microscope, a reflected electron image of the cross section of the exposed negative electrode active material layer is taken. The magnification of the reflected electron image is 3,000 to 5,000 times.

[0038] (3) The cross-sectional image obtained as described above is read into a computer and binarized using image analysis software (e.g., ImageJ, manufactured by the National Institutes of Health, U.S.A.) to obtain a binary processed image in which the particle cross section in the cross-sectional image is converted into black and the voids in the particle cross section are converted into white.

[0039] (4) Graphite particles A and B with a particle size of 5 μm to 50 μm are selected from the binary processed image, and the area of ​​the cross section of the graphite particles and the area of ​​the internal voids present in the cross section of the graphite particles are calculated. Here, the area of ​​the cross section of the graphite particles refers to the area of ​​the region surrounded by the periphery of the graphite particles, that is, the total area of ​​the cross section of the graphite particles. In addition, for the voids with a width of less than 3 μm in the cross section of the graphite particles, it is sometimes difficult to distinguish whether they are internal voids or external voids in image analysis. Therefore, the voids with a width of less than 3 μm can be regarded as internal voids. Then, the internal void ratio of the graphite particles is calculated based on the calculated area of ​​the cross section of the graphite particles and the area of ​​the internal voids in the cross section of the graphite particles (area of ​​the internal voids in the cross section of the graphite particles × 100 / area of ​​the cross section of the graphite particles). The internal void ratio of graphite particles A and B is the average value of 10 graphite particles A and B respectively.

[0040] The graphite particles A and B are produced, for example, as follows.

[0041] <Graphite Particle A Having an Internal Porosity of 5% or Less>

[0042] For example, the coke (precursor) to be the main raw material is crushed into a specified size, and in a state where they are agglomerated with a binder, they are sintered at a temperature above 2600°C, graphitized, and then sieved to obtain graphite particles A of the desired size. Here, the internal porosity can be adjusted to less than 5% according to the particle size of the precursor after crushing, the particle size of the precursor in an agglomerated state, etc. For example, the average particle size (volume-based median particle size D50) of the crushed precursor is preferably in the range of 12μm to 20μm. In addition, when the internal porosity is reduced in a range of less than 5%, it is preferred to increase the particle size of the crushed precursor.

[0043] <Graphite particles B having an internal porosity of 8% to 20%>

[0044] For example, the coke (precursor) to be the main raw material is crushed into a specified size, agglomerated with a binder, and then pressed into a block state, and fired at a temperature of 2600°C or above to graphitize it. The block-shaped molded body after graphitization is crushed and sieved to obtain graphite particles B of the desired size. Here, the internal porosity can be adjusted to 8% to 20% according to the amount of volatile components added to the block-shaped molded body. In the case where a part of the binder added to the coke (precursor) volatilizes during firing, the binder can be used as a volatile component. Asphalt can be exemplified as such a binder.

[0045] The graphite particles A and B used in this embodiment are natural graphite, artificial graphite, etc., without particular limitation. From the perspective of the ease of adjusting the internal porosity, artificial graphite is preferred. The interplanar spacing (d ) of the (002) plane of the graphite particles A and B used in this embodiment based on the wide-angle X-ray diffraction method is 002 ) is preferably 0.3354 nm or more, more preferably 0.3357 nm or more, and is preferably less than 0.340 nm, and more preferably 0.338 nm or less. In addition, the crystallite size (Lc(002)) of the graphite particles A and B used in the present embodiment, as determined by an X-ray diffraction method, is preferably 5 nm or more, more preferably 10 nm or more, and is preferably 300 nm or less, and more preferably 200 nm or less. The interplanar spacing (d 002 When the crystallite size (Lc(002)) and the crystallite size (Lc(002)) satisfy the above ranges, the battery capacity of the non-aqueous electrolyte secondary battery tends to be larger than when the above ranges are not satisfied.

[0046] In this embodiment, Figure 2 Compared with the region 42a on the negative electrode collector side when the negative electrode active material layer 42 is divided into two equal parts in the thickness direction, the graphite particles A are contained more in the region 42b on the outer surface side. As a result, for example, the decomposition reaction of the non-aqueous electrolyte at the negative electrode is suppressed under high temperature environment, and therefore, the expansion of the battery caused by gas generation during high temperature storage is suppressed. It should be noted that dividing the negative electrode active material layer 42 into two equal parts in the thickness direction means that when the stacking direction of the negative electrode collector 40 and the negative electrode active material layer 42 is set as the thickness direction of the negative electrode active material layer 42, the negative electrode active material layer 42 is divided into two halves at the middle Z of the thickness. Moreover, when the negative electrode active material layer 42 is divided into two equal parts in the thickness direction, the negative electrode active material layer 42 located near when viewed from the negative electrode collector 40 is set as the region 42a on the negative electrode collector side, and the negative electrode active material layer 42 located far when viewed from the negative electrode collector 40 is set as the region 42b on the outer surface side.

[0047] In the present embodiment, the graphite particles A may be contained more in the region 42b on the outer surface side than in the region 42a on the negative electrode current collector side. However, from the perspective of suppressing the expansion of the battery caused by gas generation during high-temperature storage, the ratio of the graphite particles A to the graphite particles B in the region 42b on the outer surface side is preferably 20:80 to 100:0, and more preferably 50:50 to 100:0 in terms of mass ratio. In addition, the ratio of the graphite particles A to the graphite particles B in the region 42a on the negative electrode current collector side is preferably 10:90 to 0:100 in terms of mass ratio, and more preferably 0:100.

[0048] An example of a method for preparing the negative electrode active material layer 42 is described. For example, a negative electrode active material containing graphite particles B (containing graphite particles A as needed), a binder, and a solvent such as water are mixed to prepare a negative electrode mixture slurry for the negative electrode collector side. Alternatively, a negative electrode active material containing a larger amount of graphite particles A (containing graphite particles B as needed) than the negative electrode mixture slurry for the negative electrode collector side, a binder, and a solvent such as water are mixed to prepare a negative electrode mixture slurry for the outer surface side. Then, after the negative electrode mixture slurry for the negative electrode collector side is applied to both sides of the negative electrode collector and dried, the negative electrode mixture slurry for the outer surface side is applied to both sides of the coating formed by the negative electrode mixture slurry for the negative electrode collector side and dried, thereby forming the negative electrode active material layer 42. In the above method, after the negative electrode mixture slurry for the negative electrode collector side is applied and dried, the negative electrode mixture slurry for the outer surface side is applied, but it can also be a method in which the negative electrode mixture slurry for the negative electrode collector side is applied and before drying before the negative electrode mixture slurry for the outer surface side is applied, and the negative electrode mixture slurry for the negative electrode collector side and the negative electrode mixture slurry for the outer surface side can also be applied at the same time.

[0049] The negative electrode active material may include other materials that can reversibly absorb and release lithium ions, such as Si-based materials, in addition to the graphite particles A and B used in this embodiment. Examples of Si-based materials include Si, alloys containing Si, and SiO x (x is 0.8 to 1.6) and other silicon oxides. Si-based materials are negative electrode materials that can increase battery capacity compared to graphite particles, but on the other hand, they have a large volume expansion during charge and discharge, so they are disadvantageous in terms of charge and discharge cycle characteristics. However, in a negative electrode active material layer having a negative electrode active material containing graphite particles A, B and Si-based materials, when the amount of graphite particles A is more in the area of ​​half of the outer surface side than in the area of ​​half of the negative electrode collector side, the reduction in charge and discharge cycle characteristics can sometimes be effectively suppressed. From the perspective of increasing battery capacity and suppressing the reduction in charge and discharge cycle characteristics, the content of Si-based materials is preferably 1% to 10% by mass, and more preferably 3% to 7% by mass, relative to the mass of the negative electrode active material.

[0050] As other materials that can reversibly absorb and release lithium ions, metals alloyed with lithium such as tin (Sn), and alloys and oxides containing metal elements such as Sn can also be cited. The negative electrode active material can contain the above-mentioned other materials, and the content of the above-mentioned other materials is preferably less than 10% by mass relative to the mass of the negative electrode active material.

[0051] Examples of the binder include fluorine resins, PAN, polyimide resins, acrylic resins, polyolefin resins, styrene-butadiene rubber (SBR), nitrile rubber (NBR), carboxymethyl cellulose (CMC) or its salts, polyacrylic acid (PAA) or its salts (PAA-Na, PAA-K, etc., and partially neutralized salts), polyvinyl alcohol (PVA), etc. These may be used alone or in combination of two or more.

[0052] [positive electrode]

[0053] The positive electrode 11 is composed of, for example, a positive electrode current collector such as a metal foil and a positive electrode active material layer formed on the positive electrode current collector. The positive electrode current collector may be a foil of a metal such as aluminum that is stable within the potential range of the positive electrode, or a film having the metal disposed on the surface. The positive electrode active material layer may include, for example, a positive electrode active material, a binder, a conductive agent, and the like.

[0054] The positive electrode 11 can be produced, for example, by applying a positive electrode mixture slurry containing a positive electrode active material, a binder, a conductive agent, etc., on a positive electrode current collector, drying the mixture to form a positive electrode active material layer, and then rolling the positive electrode active material layer.

[0055] Examples of the positive electrode active material include lithium transition metal oxides containing transition metal elements such as Co, Mn, and Ni. Examples of lithium transition metal oxides include Li x CoO2、Li x NiO2、Li x MnO2、Li x Co y Ni1- y O2、Li x Co y M 1-y O z , Li x Ni 1- y M y O z , Li x Mn2O4、Li x Mn 2-y M y O4, LiMPO4, Li2MPO4F (M; at least one of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, B, 0<x≤1.2, 0<y≤0.9, 2.0≤z≤2.3). They can be used alone or in combination. From the perspective of achieving a high capacity of a non-aqueous electrolyte secondary battery, the positive electrode active material preferably contains Li x NiO2、Li x Coy Ni 1-y O2、Li x Ni 1-y M y O z Lithium nickel composite oxides such as (M; at least one of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, B, 0<x≤1.2, 0<y≤0.9, 2.0≤z≤2.3).

[0056] Examples of the conductive agent include carbon black (CB), acetylene black (AB), Ketjen black, graphite and other carbon particles, etc. These may be used alone or in combination of two or more.

[0057] Examples of the binder include fluorine-based resins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide-based resins, acrylic resins, and polyolefin-based resins, etc. These may be used alone or in combination of two or more.

[0058] [Non-aqueous electrolyte]

[0059] The non-aqueous electrolyte contains a diisocyanate compound. Furthermore, by containing the diisocyanate compound, for example, the decomposition reaction of the non-aqueous electrolyte at the positive electrode is suppressed in a high temperature environment, and thus the expansion of the battery caused by gas generation during high temperature storage is suppressed.

[0060] The diisocyanate compound is not particularly limited as long as it is a compound having two isocyanate groups in one molecule. From the perspective of effectively suppressing the expansion of the battery caused by gas generation during high-temperature storage, it is preferably a diisocyanate compound represented by the general formula: O=C=NRN=C=O (wherein R is an aliphatic hydrocarbon group optionally having a heteroatom or an aromatic hydrocarbon group optionally having a heteroatom). The aliphatic hydrocarbon group may be linear or branched.

[0061] The carbon number of the aliphatic hydrocarbon group is preferably, for example, in the range of 1 to 12, more preferably in the range of 2 to 10. In addition, the carbon number of the aromatic hydrocarbon group is preferably, for example, in the range of 6 to 20, more preferably in the range of 8 to 18. When the carbon number of the aliphatic hydrocarbon group and the carbon number of the aromatic hydrocarbon group exceed the above range, the viscosity of the nonaqueous electrolyte becomes higher than that in the above range, for example, and the resistance of the nonaqueous electrolyte secondary battery may increase.

[0062] Examples of the aliphatic hydrocarbon group include an alkyl group, an alkenyl group, an alkynyl group, etc. Examples of the aromatic hydrocarbon group include a phenyl group, a tolyl group, a benzyl group, a phenethyl group, etc.

[0063] The aliphatic hydrocarbon group and the aromatic hydrocarbon group may have a hetero atom substituted with a hydrogen atom or a carbon atom. The hetero atom is not particularly limited, and examples thereof include boron, silicon, nitrogen, sulfur, fluorine, chlorine, and bromine.

[0064] Examples of the diisocyanate compound represented by the general formula include 1,4-diisocyanatobutane, 1,5-diisocyanatopentane, 1,6-diisocyanatohexane, 1,7-diisocyanatoheptane, 1,8-diisocyanatooctane, 1,9-diisocyanatononane, 1,10-diisocyanatodecane, toluene diisocyanate, xylene diisocyanate, toluene diisocyanate, 1,3-bis(isocyanatemethyl)cyclohexane, dicyclohexylmethane-1,1′-diisocyanate, dicyclohexylmethane-2,2′-diisocyanate, dicyclohexylmethane-3,3′-diisocyanate, dicyclohexylmethane-4,4′-diisocyanate, and isophorone diisocyanate. Among these, 1,6-diisocyanatohexane is preferred from the viewpoint of suppressing the expansion of the battery caused by gas generation during high-temperature storage and suppressing the resistance increase of the non-aqueous electrolyte secondary battery. These may be used alone or in combination of two or more.

[0065] The content of the diisocyanate compound in the non-aqueous electrolyte is preferably in the range of 0.01% by mass to 3% by mass, more preferably in the range of 0.05% by mass to 2% by mass, and further preferably in the range of 0.1% by mass to 1% by mass. When the content of the diisocyanate compound satisfies the above range, it is possible to suppress the reduction of battery characteristics and suppress the expansion of the battery caused by gas generation during high temperature storage compared to the case where the content of the diisocyanate compound does not satisfy the above range.

[0066] The non-aqueous electrolyte solution contains an electrolyte salt. The electrolyte salt is preferably a lithium salt. Examples of lithium salts include LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiAlCl4, LiSCN, LiCF3SO3, LiCF3CO2, Li(P(C2O4)F4), LiPF 6-x (C n F 2n+1 ) x (1<x<6, n is 1 or 2), LiB 10 Cl 10 , LiCl, LiBr, LiI, lithium chloroborane, lower aliphatic carboxylic acid lithium, Li2B4O7, Li(B(C2O4)F2) and other borates, LiN(SO2CF3)2, LiN(C1F 2l+1 SO2)(C m F 2m+1SO2) {l, m is an integer greater than 0} and other imide salts. The lithium salt may be used alone or in combination. Among these, LiPF6 is preferably used from the viewpoints of ion conductivity, electrochemical stability, etc. The concentration of the lithium salt is preferably set to 0.8 to 1.8 mol per 1L of the non-aqueous solvent.

[0067] The non-aqueous electrolyte solution includes, for example, a non-aqueous solvent that dissolves an electrolyte salt. Examples of the non-aqueous solvent include esters, ethers, nitriles such as acetonitrile, amides such as dimethylformamide, and mixed solvents of two or more thereof. The non-aqueous solvent may contain a halogen-substituted product in which at least a portion of hydrogen atoms of these solvents are replaced by halogen atoms such as fluorine.

[0068] Examples of the esters include cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate; chain carbonates such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), methyl propyl carbonate, ethyl propyl carbonate, and methyl isopropyl carbonate; cyclic carboxylates such as γ-butyrolactone and γ-valerolactone; and chain carboxylates such as methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), and ethyl propionate.

[0069] Examples of the ethers include 1,3-dioxolane, 4-methyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, propylene oxide, 1,2-butylene oxide, 1,3-dioxane, 1,4-dioxane, 1,3,5-trioxane, furan, 2-methylfuran, 1,8-cineole, cyclic ethers such as crown ether, 1,2-dimethoxyethane, diethyl ether, dipropyl ether, diisopropyl ether, dibutyl ether, dihexyl ether, ethylethylene. Chain ethers such as 1,2-dimethoxyethane, 1,2-dibutoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, 1,1-dimethoxymethane, 1,1-diethoxyethane, methyl phenyl ether, ethyl phenyl ether, butyl phenyl ether, pentyl phenyl ether, methoxytoluene, benzyl ethyl ether, diphenyl ether, dibenzyl ether, o-dimethoxybenzene, 1,2-diethoxyethane, 1,2-dibutoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, 1,1-dimethoxymethane, 1,1-diethoxyethane, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, etc.

[0070] As the halogen-substituted product, preferably used are fluorinated cyclic carbonates such as fluoroethylene carbonate (FEC), fluorinated chain carbonates, fluorinated chain carboxylates such as fluoromethyl propionate (FMP), and the like.

[0071] [Spacer]

[0072] For example, a porous sheet having ion permeability and insulation can be used as the spacer 13. Specific examples of the porous sheet include microporous films, woven fabrics, nonwoven fabrics, etc. As the material of the spacer, olefin resins such as polyethylene and polypropylene, cellulose, etc. are preferred. The spacer 13 can be a laminate having a cellulose fiber layer and a thermoplastic resin fiber layer such as an olefin resin. In addition, it can be a multilayer spacer including a polyethylene layer and a polypropylene layer, and a spacer coated with a material such as an aramid resin, ceramics, etc. on the surface of the spacer can also be used.

[0073] Example

[0074] Hereinafter, the present invention will be further described by way of examples, but the present invention is not limited to these examples.

[0075] <Example 1>

[0076] [Production of positive electrode]

[0077] As the positive electrode active material, lithium nickel cobalt oxide (LiNi 0.88 Co 0.09 Al 0.03 O2). 100 parts by mass of positive electrode active material, 1 part by mass of acetylene black, and 0.9 parts by mass of polyvinylidene fluoride were mixed in a solvent of N-methyl-2-pyrrolidone (NMP) to prepare a positive electrode mixture slurry. The slurry was applied to both sides of an aluminum foil having a thickness of 15 μm, and after the coating was dried, the coating was rolled using a calendering roller to prepare a positive electrode having a positive electrode active material layer formed on both sides of the positive electrode collector. The prepared positive electrode was cut into a width of 57.6 mm and a length of 679 mm for use.

[0078] [Preparation of Graphite Particles A]

[0079] The coke was crushed to an average particle size (median particle size D50) of 12 μm. Pitch was added as a binder to the crushed coke to agglomerate the coke to an average particle size (median particle size D50) of 17 μm. The agglomerate was calcined at a temperature of 2800° C. to graphitize, and then sieved using a 250-mesh sieve to obtain graphite particles A having an average particle size (median particle size D50) of 23 μm.

[0080] [Preparation of Graphite Particles B]

[0081] The coke was pulverized to an average particle size (median particle size D50) of 15 μm, and pitch was added as a binder to the pulverized coke to agglomerate it. Then, a 1.6 g / cm 3 ~1.9g / cm 3The block-shaped body is sintered at a temperature of 2800°C to graphitize. Next, the block-shaped body after graphitization is crushed and sieved using a 250-mesh sieve to obtain graphite particles B with an average particle size (median particle size D50) of 23 μm.

[0082] [Production of negative electrode]

[0083] Graphite particles A were mixed in an amount of 40 parts by mass, graphite particles B were mixed in an amount of 55 parts by mass, and SiO was mixed in an amount of 5 parts by mass, and this was used as the negative electrode active material A contained in the half region on the outer surface side of the negative electrode active material layer. Negative electrode active material A: carboxymethyl cellulose (CMC): styrene-butadiene copolymer rubber (SBR) were mixed in an amount of 100:1:1 by mass, and a negative electrode mixture slurry on the outer surface side was prepared. In addition, graphite particles B were mixed in an amount of 95 parts by mass, and SiO was mixed in an amount of 5 parts by mass, and this was used as the negative electrode active material B contained in the half region on the negative electrode current collector side of the negative electrode active material layer. Negative electrode active material B: carboxymethyl cellulose (CMC): styrene-butadiene copolymer rubber (SBR) were mixed in an amount of 100:1:1 by mass, and a negative electrode mixture slurry on the negative electrode current collector side was prepared.

[0084] The negative electrode mixture slurry on the negative electrode collector side is applied to both sides of a copper foil with a thickness of 8 μm. After the coating is dried, the negative electrode mixture slurry on the outer surface side is applied to the coating and dried, and the coating is rolled using a calendering roller to produce a negative electrode having a negative electrode active material layer formed on both sides of the negative electrode collector. That is, the mass ratio of graphite particles A: graphite particles B in the outer surface side half of the active material layer is 40:55, and the mass ratio of graphite particles A: graphite particles B in the negative electrode collector side half of the negative active material layer is 0:100. In addition, in the produced negative electrode, the internal porosity of graphite particles A and B was measured, and the results were 3% and 15%, respectively. The produced negative electrode was cut into a width of 58.6 mm and a length of 662 mm for use.

[0085] [Preparation of non-aqueous electrolyte]

[0086] In a non-aqueous solvent prepared by mixing ethylene carbonate (EC), ethyl methyl carbonate (MEC) and dimethyl carbonate (DMC) in a volume ratio of 20:5:75, LiPF6 was dissolved at a concentration of 1.4 mol / L, and 3% by mass of vinylene carbonate and 0.5% by mass of 1,6-diisocyanatohexane were further added to prepare a non-aqueous electrolyte.

[0087] [Manufacturing of non-aqueous electrolyte secondary battery]

[0088] (1) An aluminum positive electrode lead was attached to a positive electrode current collector and a nickel-copper-nickel negative electrode lead was attached to a negative electrode current collector. The positive electrode and the negative electrode were then wound with a polyethylene separator interposed therebetween to prepare a wound electrode assembly.

[0089] (2) Insulating plates are disposed above and below the electrode body, respectively, the negative electrode lead is welded to the case body, the positive electrode lead is welded to the sealing body, and the electrode body is housed in the case body.

[0090] (3) After injecting a nonaqueous electrolyte into the case body by decompression, the open end of the case body is rivet-jointed to the sealing body via a gasket to prepare a nonaqueous electrolyte secondary battery.

[0091] <Comparative Example 1>

[0092] Graphite particles B are mixed in a manner of 95 parts by mass and SiO is mixed in a manner of 5 parts by mass, and this is used as the negative electrode active material C contained in the entire region of the negative electrode active material layer. The negative electrode active material C: carboxymethyl cellulose (CMC): styrene-butadiene copolymer rubber (SBR) are mixed in a manner of a mass ratio of 100:1:1 to prepare a negative electrode mixture slurry. The negative electrode mixture slurry is applied to both sides of a copper foil having a thickness of 8 μm, and after the coating is dried, the coating is rolled by a calendering roll, thereby preparing a negative electrode having a negative electrode active material layer formed on both sides of the negative electrode collector. That is, the graphite particles A: graphite particles B in the outer surface side half of the negative electrode active material layer are 0:100 in mass ratio, and the graphite particles A: graphite particles B in the negative electrode collector side half of the negative electrode active material layer are also 0:100 in mass ratio. The prepared negative electrode is cut into a width of 58.6 mm and a length of 662 mm for use.

[0093] In a non-aqueous solvent prepared by mixing ethylene carbonate (EC), ethyl methyl carbonate (MEC), and dimethyl carbonate (DMC) in a volume ratio of 20:5:75, LiPF6 was dissolved at a concentration of 1.4 mol / L, and 3% by mass of vinylene carbonate was further added to form a non-aqueous electrolyte. That is, a non-aqueous electrolyte not containing a diisocyanate compound was used in Comparative Example 1.

[0094] A nonaqueous electrolyte secondary battery was produced in the same manner as in Example 1 using the above negative electrode and the nonaqueous electrolyte.

[0095] <Comparative Example 2>

[0096] A nonaqueous electrolyte secondary battery was produced in the same manner as in Example 1 except that the negative electrode produced in Comparative Example 1 was used.

[0097] <Comparative Example 3>

[0098] A nonaqueous electrolyte secondary battery was produced in the same manner as in Example 1 except that the nonaqueous electrolyte prepared in Comparative Example 1 was used.

[0099] [High temperature storage test]

[0100] After the non-aqueous electrolyte secondary batteries of Example 1 and each comparative example were charged to 4.2V at a constant current of 990mA (0.3 hour rate) at an ambient temperature of 25°C, they were charged to a constant voltage of 66mA with a constant voltage of 4.2V. Then, constant current discharge was performed to 3.0V at a constant current of 1650mA (0.5 hour rate). Then, a laser displacement meter was used to measure the height of the central part of the tank bottom in the height direction of the battery with the outer peripheral end of the tank bottom of the shell body as the reference, and it was used as the height of the central part of the tank bottom before storage.

[0101] Next, constant current charging was performed at a constant current of 990 mA (0.3 hour rate) to 4.2 V, and constant voltage charging was performed at a constant voltage of 4.2 V with a termination current set to 66 mA, and then stored in a thermostatic bath at 80° C. for 3 days. Each nonaqueous electrolyte secondary battery after storage was taken out of the thermostatic bath, left for 1 hour, and then discharged at a constant current of 1650 mA (0.5 hour rate) to 3.0 V at an ambient temperature of 25° C. Then, a laser displacement meter was used to measure the height of the central part of the tank bottom in the height direction of the battery with the outer peripheral end of the tank bottom of the shell body as the reference, and it was used as the height of the central part of the tank bottom after storage.

[0102] Then, the expansion amount of the battery was calculated by subtracting the height of the center of the bottom of the can before storage from the measured height of the center of the bottom of the can after storage, and the result is summarized in Table 1. Here, the main cause of battery expansion is gas generation caused by decomposition of the non-aqueous electrolyte during high-temperature storage. Therefore, the smaller the expansion amount of the battery calculated, the more gas generation during high-temperature storage is suppressed.

[0103] [Table 1]

[0104]

[0105] As can be seen from Table 1, the amount of expansion of the battery of Example 1 is smaller than that of Comparative Examples 1 to 3. That is, according to Example 1, the amount of expansion of the battery due to gas generation during high-temperature storage can be suppressed.

[0106] Description of Reference Numerals

[0107] 10 non-aqueous electrolyte secondary battery, 11 positive electrode, 12 negative electrode, 13 separator, 14 electrode body, 15 battery case, 16 case body, 17 sealing body, 18, 19 insulating plate, 20 positive electrode lead, 21 negative electrode lead, 22 bulging portion, 23 filter, 24 lower valve body, 25 insulating member, 26 upper valve body, 27 cover, 28 gasket, 30 graphite particles, 34 internal voids, 36 external voids, 40 negative electrode collector, 42 negative electrode active material layer, 42a half of the area on the negative electrode collector side, 42b half of the area on the outer surface side.

Claims

1. A non-aqueous electrolyte secondary battery, comprising a positive electrode, a negative electrode, and a non-aqueous electrolyte, wherein: The negative electrode comprises a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector. The negative electrode active material layer contains graphite particles A and graphite particles B as negative electrode active materials. The internal porosity of the graphite particles A is less than 5%, and the internal porosity of the graphite particles B is 8% to 20%. The graphite particles A are contained more in the half region on the outer surface side than in the half region on the negative electrode current collector side when the negative electrode active material layer is divided into two equal parts in the thickness direction, The nonaqueous electrolyte contains a diisocyanate compound.

2. The nonaqueous electrolyte secondary battery according to claim 1, wherein: The diisocyanate compound is represented by the general formula: O=C=NRN=C=O, In the formula, R is an aliphatic hydrocarbon group which may have a hetero atom or an aromatic hydrocarbon group which may have a hetero atom.

3. The non-aqueous electrolyte secondary battery according to claim 2, wherein: The aliphatic hydrocarbon group has 1 to 12 carbon atoms, and the aromatic hydrocarbon group has 6 to 20 carbon atoms.

4. The nonaqueous electrolyte secondary battery according to any one of claims 1 to 3, wherein The content of the diisocyanate compound in the non-aqueous electrolyte is in the range of 0.01% by mass to 3% by mass.

5. The nonaqueous electrolyte secondary battery according to any one of claims 1 to 3, wherein The negative electrode active material includes a Si-based material.

6. The nonaqueous electrolyte secondary battery according to claim 4, wherein: The negative electrode active material includes a Si-based material.

Citation Information

Patent Citations

  • Electrochemical battery fined carbon

    JP1997320600A

  • Battery and electrolyte composition

    JP2007242411A

  • Carbon material for nonaqueous secondary battery, negative electrode, and nonaqueous secondary battery

    JP2014067638A

  • Electrode for secondary battery

    JP2015049965A

  • Electrode and power storage device

    JP2018156787A